Security, privacy and anonymity in computation, communication and storage : SpaCCS 2016 International Workshops, TrustData, TSP, NOPE, DependSys, BigDataSPT, and WCSSC, Zhangjiajie, China, November 16-18, 2016, Proceedings /: SpaCCS 2016 International Workshops, TrustData, TSP, NOPE, DependSys, BigDataSPT, and WCSSC, Zhangjiajie, China, November 16-18, 2016, Proceedings. (2016) - Unknown
No abstract available